Simple and sensitive high performance liquid chromatographic (HPLC) method for the determination of the selegiline in human plasma - Hossein Danafar (Cogent Medicine, 2016)
Selegiline is best known as an irreversible inhibitor of monoamine oxidase (MAO), an intracellular enzyme associated with the outer membrane of mitochondria. The purpose of this study is to establish a reliable and quick method for the assignment of selegiline in human plasma by high performance liquid chromatography with ultraviolet detection. A rapid and sensitive high performance liquid chromatographic (HPLC) method has been developed for determination of selegiline in human plasma. The method uses a protein precipitation step with methanol. Mobile phase was composed of phosphate buffer 0.1 M (pH 6.5)-acetonitrile (70:30 v/v) with a flow rate of 1 ml/min. The eluted peaks were detected by a UV detector was set at wavelength of 205 nm. The method was validated in the range of selegiline concentrations from 10 to 100 ng/ml. The limits of detection and quantitation of the method were 5 and 10 ng/ml, respectively. The average drug recovery from plasma was 98.20% throughout the linear concentration range. The average within-run and between-run accuracy values of 99.24 and 98.78, respectively. The method is quick, easy, very steady, and precise for the screen, assignment, and evaluation of selegiline in human plasma by HPLC.